2020
DOI: 10.15344/2456-8007/2020/148
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Guidelines Changing Faster than the Virus: Implications of a Clinical Decision Support App

Abstract: Novel coronavirus disease (COVID-19) is a pandemic affecting over 10 million people in 160 countries. Its spread, and the medical communities’ response, cast light on an important deficiency in the speed and effectiveness for evidence-based recommendations to reach the bedside in academic medical practice. We built a clinical decision support tool on the avoMD platform that systematizes and personalizes the treatment of COVID-19 by bringing point-of-care access to the guidelines specific to individual cases to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…This issue is pertinent in the case of novel conditions like COVID-19, where best practice changes frequently as more management options are discovered. 7 Overall, our results suggest there was greater understanding about the importance of anti-S antibody requesting over the 4-month intervention period. Our findings agree with research that has suggested a mixture of educational sessions and visual reminders increase application of guidelines in clinical practice.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This issue is pertinent in the case of novel conditions like COVID-19, where best practice changes frequently as more management options are discovered. 7 Overall, our results suggest there was greater understanding about the importance of anti-S antibody requesting over the 4-month intervention period. Our findings agree with research that has suggested a mixture of educational sessions and visual reminders increase application of guidelines in clinical practice.…”
Section: Discussionmentioning
confidence: 66%
“…This issue is pertinent in the case of novel conditions like COVID-19, where best practice changes frequently as more management options are discovered. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most CDS developed to date focus on single decision points and less on comprehensive disease-specific decision support spanning the duration of hospitalization. As a solution, we suggest creating a multifaceted CDSS that addresses care across the spectrum of a disease; this has also been suggested in the literature but has not been extensively studied [ 56 , 57 ]. A CDSS that incorporates all phases of care, from admission orders and imaging to discharge and follow-up, could be built to avoid redundancy as well.…”
Section: Discussionmentioning
confidence: 99%
“…Some effective public health measures, prevention strategies, and therapeutics options are now available, but international, national, and subnational policies do not always follow shared guidelines, creating confusion and mistrust among the general population [3][4][5]. This issue is partially determined by a gap between data collection, scientific evidence, their validation, and the creation/modification of the guidelines [6]. The forced cohabitation with SARS-CoV-2 has made it even clearer that there is great importance in making validated and updated scientific information available to policy makers, healthcare professionals, and the public as quickly as possible.…”
Section: Introductionmentioning
confidence: 99%